(3GdahGFO GdLOjOIs - (3GdMGFQj, GdhMjO GdHgHgGfj, CMeO Hf eMeO Ydj Hf eMeO HGbQ, J(B1243(3g`s ((3CHh GdbGSe Hf Ydfjbi Hf eMeO LhGOs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf MeOG dG jbhi Ydi EMUGFg GdG gh (B... (3CeG HYO aEfg deG HYO GdYgO Yf ReGf GdCFeI hNaj CeGQGJ Gdabg hGdCOdI(B...s
(3BNQgG (B:s
(3heY Pdc ZGjI eG aj GdHGH Cf jchf GdYGde aj NUhU gPg GdeSCdI jMJGW hdG jLhR dg GdYed HGLJgGOg ceG YQaJ(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B281s
(3GdPQjYI(B:(3L(B16(3,U(B234(3,Qbe(B1529/ (3GdPQjYI(B:(3L(B22(3,U(B124(3,JMJ Qbe (B6682s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs